THE MODELS OF LEARNING SOFTWARE ACCESS IN THE CLOUD BASED EDUCATIONAL ENVIRONMENT (Journal of Information Technologies in Education (ITE), 2015)
In the modern information-educational environment there are new models of learning activity based on innovative technological solutions for the organization of the environment infrastructure , which include the cloud-oriented solutions.     The problems of the institution information technological infrastructure setup for the needs of users, the organization of tools and services of that environment so as to allow maximum pedagogical advantage of modern ICT to achieve improvement of learning outcomes and the processes of scientific and educational activities organization, require justification of the ways to provide access to software and electronic educational resources.     The article outlines the conceptual framework of the study and review existing approaches,tools, model of a cloud-based environment, their advantages and disadvantages, experience of use.The models of environment architecture, the peculiarities of its pedagogical application are exposed. The hybrid service model of access to software for educational purposes is grounded.     The aim of research is an analysis of thy modern approaches to the formation of the cloudbased learning environment of the institution on the basis of different types of service models;justification of the hybrid service model of the learning software access.
Keywords: cloud technology; learning environment; higher education institution; the hybrid service model; electronic educational resources